2016
DOI: 10.1161/atvbaha.115.307031
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Deficiency in Macrophages Inhibits Neointimal Hyperplasia and Suppresses Macrophage Inflammation Through SGK1-AP1/NF-κB Pathways

Abstract: Objective-Restenosis after percutaneous coronary intervention remains to be a serious medical problem. Although mineralocorticoid receptor (MR) has been implicated as a potential target for treating restenosis, the cellular and molecular mechanisms are largely unknown. This study aims to explore the functions of macrophage MR in neointimal hyperplasia and to delineate the molecular mechanisms. Approach and Results-Myeloid MR knockout (MMRKO) mice and controls were subjected to femoral artery injury.MMRKO reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 33 publications
4
54
0
1
Order By: Relevance
“…Myeloid deficiency in mineralocorticoid receptor attenuated vascular inflammation in a model of femoral artery injury and led to reduced macrophage migration, proliferation, and activation, in association with reduced activation of AP1/NF-κB pathways. 51 The results are consistent with the atheroprotective phenotype of serum-and glucocorticoid-inducible kinase-1 deficiency in Apoe −/− mice, which was also attributed to reduced NF-κB activation in macrophages. 52 NF-κB signaling is generally considered as proatherogenic, although its activation in macrophages may lead to atheroprotection in some settings.…”
Section: Innate Immune Functionssupporting
confidence: 80%
“…Myeloid deficiency in mineralocorticoid receptor attenuated vascular inflammation in a model of femoral artery injury and led to reduced macrophage migration, proliferation, and activation, in association with reduced activation of AP1/NF-κB pathways. 51 The results are consistent with the atheroprotective phenotype of serum-and glucocorticoid-inducible kinase-1 deficiency in Apoe −/− mice, which was also attributed to reduced NF-κB activation in macrophages. 52 NF-κB signaling is generally considered as proatherogenic, although its activation in macrophages may lead to atheroprotection in some settings.…”
Section: Innate Immune Functionssupporting
confidence: 80%
“…Animal studies have shown that these antagonists inhibit atherosclerosis, whereas aldosterone, an endogenous agonist of MR, promotes atherosclerosis (8,12). Utilizing a myeloid MR knock-out (MRKO) mouse model, we and others have previously demonstrated that MR regulates macrophage polarization and inflammation and that macrophage MR is important in controlling cardiac and vascular remodeling (13)(14)(15)(16)(17). However, it has remained unknown whether macrophage MR plays a role in atherosclerosis.…”
mentioning
confidence: 99%
“…The MR in target cells can be activated by aldosterone and glucocorticoids with almost identical binding affinities; unprotected MRs thus act primarily as a high-affinity GR due to the much higher circulating and intracellular concentrations of glucocorticoids. In aldosterone target cells and tissues, specificity is afforded by the expression of the 11β-hydroxysteroid dehydrogenase type II (11β-HSD2) enzyme that efficiently metabolises Protected from DOC/salt fibrosis and hypertension, protected Rickard et al (2009) Protected from L-NAME/salt fibrosis but not hypertension Bienvenu et al (2012) Reduced macrophage recruitment in stroke and AngII/L-NAME Usher et al (2010) Fibrosis, but not hypertension; protection from atherosclerosis Frieler et al (2011), Shen et al (2016 intracellular cortisol or corticosterone to inactive steroids. The MR, in contrast to the GR, which is ubiquitously expressed, has a restricted expression pattern in mammals, and is expressed in the epithelia of organs such as the kidney, colon and salivary gland, where it primarily acts as the receptor for aldosterone to regulate fluid and electrolyte/solute homeostasis.…”
Section: The Adrenal Corticosteroids Mr Signalling In Cells and Mr Amentioning
confidence: 99%
“…In an effort to determine the cellular mechanisms of MR signalling in monocytes/macrophages Usher and coworkers performed microarray on peritoneal-derived macrophages and showed MR null cells to have a gene expression pattern that overlapped with GR and PPARγ agonist activity. Shen and coworkers (2016) isolated cardiac tissue macrophages from vehicle and DOC/ salt treated mice and found that pro-inflammatory and pro-fibrotic profiles were indeed lost but the alternative activation profile was not pronounced (Shen et al 2016). Another group identified JNK signalling pathways to be MR dependent and potentially NFκB signalling (Shen et al 2016.…”
Section: Ablation Of the Mr In Specific Cellular Compartments Of The mentioning
confidence: 99%
See 1 more Smart Citation